1985
DOI: 10.1017/s0031182000049027
|View full text |Cite
|
Sign up to set email alerts
|

The identity ofLeishmania tarentolaeWenyon 1921

Abstract: A double clone of Trypanosoma platydactyli Catouillard, 1909, derived from a single trypomastigote from the blood of the Moorish gecko, Tarentola mauritanica, was grown in vitro. Morphogenesis of the parasites led to a stable population of promastigotes which were identical, in general morphology, ultrastructure and the electrophoretic mobility of 8 enzymes, to those cultures previously considered to be Leishmania tarentolae Wenyon, 1921. These cultures included the strain isolated from the type locality in Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The use of the lizard leishmania species, L. tarentolae, as a type specimen for the digenetic genus Leishmania is justified by the results of Gomez-Eichelmann et al (18), which showed that lizard leishmania species (including several strains ofL. tarentolae) are indeed more closely related to mammalian leishmania species by several criteria (kinetoplast DNA sequences, nuclear chromosomes, and membrane lipids) than to Trypanosoma species, as has been suggested by Wallbanks et al (19).…”
Section: Methodsmentioning
confidence: 96%
“…The use of the lizard leishmania species, L. tarentolae, as a type specimen for the digenetic genus Leishmania is justified by the results of Gomez-Eichelmann et al (18), which showed that lizard leishmania species (including several strains ofL. tarentolae) are indeed more closely related to mammalian leishmania species by several criteria (kinetoplast DNA sequences, nuclear chromosomes, and membrane lipids) than to Trypanosoma species, as has been suggested by Wallbanks et al (19).…”
Section: Methodsmentioning
confidence: 96%
“…Recently, it has been shown that parasites identified as Trypanosoma platydactylii were identical by isoenzyme profiles to existing laboratory stocks of L. tarentolae (43). The nomenclature and identity of these strains have been called into question (19a, 43), and in this report we refer to these species as L. tarentolae.…”
Section: Methodsmentioning
confidence: 91%
“…
Box 1. Commercial eukaryotic protein expression systemsThe protozoan Leishmania tarentolae , which was isolated from the Moorish gecko Tarentola mauritanica [82], has been developed into a eukaryotic protein expression system (LEXSY, Jena Bioscience). Its eukaryotic gene expression machinery, which includes full glycosylation and disulfide bond formation, represents a potential advantage over other expression systems.
…”
Section: Discussionmentioning
confidence: 99%